2012 International Conference on Biomedical Engineering and Biotechnology 2012
DOI: 10.1109/icbeb.2012.349
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adsorption of Flavonoids on Chitosan Resin Grafted by Quercetin

Abstract: Chitosan resin grafted by quercetin (QCR), the adsorbent, was used as for the separation of flavonoids. The optimum conditions were determined by automatic liquid chromatography system. Moreover, the hydrophobic interaction between the flavonoids and QCR could be useful for the effective adsorption and separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…As this adsorption was facilitated by incorporating quercetin into the resin, this same kind of mechanism was already reported (Zhang et at., 2012).…”
Section: Marine Biopolymers Such As Proteins and Polysaccharides Are ...supporting
confidence: 70%
See 1 more Smart Citation
“…As this adsorption was facilitated by incorporating quercetin into the resin, this same kind of mechanism was already reported (Zhang et at., 2012).…”
Section: Marine Biopolymers Such As Proteins and Polysaccharides Are ...supporting
confidence: 70%
“…Hence the high adsorption capacity and purity of flavonoids could be attained (Zhou et al., 2011). As this adsorption was facilitated by incorporating quercetin into the resin, this same kind of mechanism was already reported (Zhang et at., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Literature suggests that flavonoid-type compounds can establish different interactions with protein-like fibers such as ubiquitous van der Waals forces, hydrogen bonds, and electrostatic and hydrophobic interactions [ 36 ]. Previous studies have shown that the adsorption of quercetin onto PA fibers is significantly higher than the adsorption of rutin [ 35 ] and can establish more firm hydrophobic interactions with chitosan resins [ 37 ]. Figure 6 represents simplified binding interactions of quercetin and tangeretin, as examples, with WO, PA, and CA fiber surfaces, while other extract compounds are supposed to behave in a similar manner.…”
Section: Resultsmentioning
confidence: 99%